PENERAPAN STRATEGI PEMBELAJARAN STAD (STUDENT TEAMS ACHIEVEMENT DIVISION) BERBANTUAN KUIS INTERAKTIF UNTUK MENINGKATKAN KEMAMPUAN LITERASI MEMBACA PESERTA DIDIK KELAS V DI SDN 238 PALEMBANG - Patricia, Putri; Ernalida; Putri, Ineke; Sari, Imelda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve the reading literacy skills of fifth-grade students at SDN 238 Palembang in the Indonesian language subject through the implementation of the Student Teams Achievement Division (STAD) learning strategy assisted by interactive quizzes. The main problem faced is the low level of students’ reading literacy skills, as indicated only 7.41% of students achieving the Minimum Completeness Criteria (KKM) before the intervention. This research is a Classroom Action Research (PTK) conducted in two cycles, which included the stages of planning, implementation, observation, and reflection. The results showed a significant improvement in students’ reading literacy skills. In the first cycle, learning mastery reached 48.1% with an average score of 63.5, and in the second cycle, it increased to 81.4% with an average score of 81.1. The implementation of interactive quizzes such as Wordwall and Baamboozle in the STAD strategy also proved effective in enhancing active participation, collaboration, and students’ learning motivation. Therefore, the STAD learning strategy assisted by interactive quizzes can be considered an effective alternative teaching strategy to improve reading literacy skills at the elementary school level.